2018
DOI: 10.3389/fpsyg.2018.00519
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties and Measurement Invariance of the Brief Symptom Inventory-18 Among Chinese Insurance Employees

Abstract: This study aimed to examine the psychometric properties and factorial invariance of the Brief Symptom Inventory-18 (BSI-18). Confirmatory factor analyses (CFAs) were performed to verify the BSI-18’s factor structure in a large sample of Chinese insurance professionals (N = 2363, 62.7% women; age range = 19–70). Multigroup CFA were performed to test the measurement invariance of the model with the best fit across genders. In addition, structural equation modeling was conducted to test the correlations between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
24
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 33 publications
6
24
1
Order By: Relevance
“…No support was found for the hierarchical and bifactor model of the STICSA scores with a global anxiety factor and four specific factors corresponding to the four subscales of the STICSA (trait/state; cognitive/somatic) ( Roberts et al, 2016 ), nor for an oblique four-factor model of STICSA scores with factors corresponding to the somatic and cognitive subscales of the state and trait versions of the STICSA previously found in an elderly population ( Balsamo et al, 2015b ). This result was not in accordance with the increasing number of studies which have supported a bifactor structure for psychopathological scales ( Al-Turkait and Ohaeri, 2010 ; Kriston et al, 2012 ; Saggino et al, 2018 ; Wang et al, 2018 ).…”
Section: Discussioncontrasting
confidence: 78%
“…No support was found for the hierarchical and bifactor model of the STICSA scores with a global anxiety factor and four specific factors corresponding to the four subscales of the STICSA (trait/state; cognitive/somatic) ( Roberts et al, 2016 ), nor for an oblique four-factor model of STICSA scores with factors corresponding to the somatic and cognitive subscales of the state and trait versions of the STICSA previously found in an elderly population ( Balsamo et al, 2015b ). This result was not in accordance with the increasing number of studies which have supported a bifactor structure for psychopathological scales ( Al-Turkait and Ohaeri, 2010 ; Kriston et al, 2012 ; Saggino et al, 2018 ; Wang et al, 2018 ).…”
Section: Discussioncontrasting
confidence: 78%
“…This five-point Likert-like scale measures the severity of the physical and mental state of a person, from 0 (“Not at all”) to 4 (“Extremely”). It has been shown to have satisfactory internal consistency test–retest reliability [32]. The BSI-18 has four factors: somatization, depression, panic, and general anxiety; the alpha coefficients of the current sample for were .87, .86, .88, and .83, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Confirmatory factor analysis found that the three-factor model of the SMES-A had a satisfactory goodness-of-fit, indicating that it had high validity in such structures (Wang et al, 2015;Li et al, 2018). The correlation coefficients between the three factors with each other were between 0.378 and 0.482, illustrating that three facets of social media engagement composited in the SMES-A were independent and balanced.…”
Section: Discussionmentioning
confidence: 93%